Muscle activation and rating of perceived exertion of typically developing children during DRY and aquatic treadmill walking - Harrington, J. W.; Anguiano-Hernandez, J. G.; Kingston, D. C. (Journal of Electromyography and Kinesiology, 2023)
Aquatic treadmill gait training is a poorly understood rehabilitation method that alters bodyweight support, increases lower limb resistance, and assists with postural stability. This training could be an attractive tool for clinical populations with balance control issues or limited weight-bearing prescriptions for the lower limb. As a first step, the purpose of this study was to quantify differences in mean muscle activity of the tibialis anterior, rectus femoris, medial gastrocnemius, and semitendinosus, and perceived exertion (RPE) in typically developing children (7:8 M:F, age = 11.3 ± 4.1 years, 1.46 ± 0.18 m, and 44.2 ± 16.8 kg) during dry and aquatic treadmill walking at 75 %, 100 %, and 125 % self-selected speed. We hypothesized that the greatest mean muscle activity, normalized to percent maximum voluntary contraction and averaged across all strides, would be observed during 125 % dry treadmill walking and that aquatic treadmill walking would produce lower RPE. Overall, aquatic treadmill walking reduced mean medial gastrocnemius activity by 50.2 % (padj < 0.001), increased mean rectus femoris activity at least 32.8 % (padj < 0.006), and produced 78.0 % (padj = 0.007) greater RPE compared to dry treadmill walking. This study provides normative pediatric data for future aquatic treadmill walking studies in clinical populations to help inform gait rehabilitation protocols.